Recommendations for evaluating and implementing proximity warning systems on surface mining equipment - Ruff, T. M. (Dept. of Health and Human Services, Centers for Disease Control and Prevention, National Institute for Occupational Safety and Health, Spokane Research Laboratory, 2007)
"Researchers at the National Institute for Occupational Safety and Health, Spokane Research Laboratory, studied technology and methods that could reduce accidents involving surface mining equipment that collides with other vehicles or workers, or drives over an unseen road edge. These accidents are partially attributed to the lack of full visibility around these large pieces of equipment. Blind areas can be extensive and this report presents plots of blind areas for five pieces of surface mining equipment."--Page ix
Title from title screen (viewed on July 15, 2008).
"June 2007."
Keywords: Mining machinery -- Collision avoidance systems.; Mining machinery -- Safety measures.; Mineral industries.; elektronické knihy; electronic books